Optimizing the Duration of Assessment of Stage‐1 Sacral Neuromodulation in Nonobstructive Chronic Urinary Retention. Issue 1 (19th April 2013) - Elneil, Sohier; Abtahi, Bahareh; Helal, Mohamed; Digesu, Alex; Gonzales, Gwen
<x xml:space="preserve">Abstract</x> Objectives The duration of test stimulation using two‐stage sacral neuromodulation (SNM) is not studied. This study will determine the restoration of normal bladder sensation and resultant voiding in chronic urinary retention (CUR) after stage‐1 SNM. Materials and Methods Two‐stage SNM used in 24 female patients with CUR. After stage‐1 SNM, patients were assessed over an eight‐week period and asked to record the restoration of normal bladder sensation and voiding. Qualitative and quantitative statistics were used to assess the outcomes and the influence of prognostic factors. Results The mean age of patients was 37.0 ± 9.7 years. Normal bladder sensation was restored on the same day as switching on the battery after stage‐1 in seven patients (29.2%), while in 17 patients it occurred between day 2–31 (mean: nine days). Similarly, the mean onset of voiding was also nine days (range: 2–31 days). After day 15, 21% of patients voided. The mean lag time between the restoration of bladder sensation and voiding was 3.6 days. By day 17, a cumulative percentage of 90% of patients had a normalized bladder sensation and 80% had commenced voiding. Infection of the externalized lead occurred in only one case. There were no correlations between the outcome parameters with age (p > 0.05), symptom duration, or concomitant diagnosis of overactive bladder or chronic pelvic pain (p = 0.418, p = 0.114). Conclusion Stage‐1 SNM may be left in situ for up to four weeks to ensure the maximum chance of restoring normal bladder function in this complex group of patients.